Padrão motor da função manual de beber líquido em indivíduos com paralisia cerebral e desenvolvimento motor típico - Machado, Luiza Ribeiro (Universidade Federal de São Carlos, 2018)
Background: Individuals with cerebral palsy usually presents impairment of movement and posture, which causes difficulty in activities and participation of individuals, mainly when these involve the use of upper limbs. However, the control of the trunk and each segment of the upper limbs of individuals with cerebral palsy in relation to their position in space during a functional task is not well defined. Aim: To identify the coordination of the trunk and upper limbs of individuals with cerebral palsy compared to the typical ones in the task of drinking liquid from a glass. Methods: We evaluated nine individuals with cerebral palsy, mean age 9 years (± 3 years), spastic type, hemiparetic and diparetic topography, Gross Motor Function Classification System (GMFCS) levels I to IV, Manual Ability Classification System (MACS) I and II, and nine typical individuals for the comparison group, mean age 9 years (± 3 years). The individuals were seated in a chair with adjustable height and oriented to drink juice from a cup that was on the table, positioned at 75% of the length of the upper limb. The task should be performed with the preferred upper limb preferred for those typical individuals and with diparetic cerebral palsy, and non-preferred upper limb (affected) for those with hemiparetic cerebral palsy. The task of drinking juice from a cup was divided into three phases: reach, transport the cup to the mouth, and transport the cup to the table. Four Qualys Motion System cameras were used for task capture and analysis. Results: Individuals with cerebral palsy presented lower mean velocity (p<0.01) and peak velocity (p<0.01) in phases 2 and 3. They presented less rectilinear movement (p<0.01), which required more time (p=0.01) and units of motion (p<0.01) compared to typical individuals at all phases. In addition, individuals with cerebral palsy had higher trunk displacement (p=0.02) than individuals with typical motor development. Conclusion: Individuals with cerebral palsy presented lower motor coordination when compared to typical ones, which can be evidenced by slower and less rectilinear movements even when they used biomechanical compensations such as anterior trunk displacement.
Motor pattern of the manual function of drinking liquid in individuals with cerebral palsy and typical motor development
Keywords: Alcance; Cinemática; Pediatria; Avaliação; Força da mão; Transtornos motores; Gripping strength; Kinematics; Pediatrics; Evaluation; Motor disorders; Reach; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL